‘Crescendo transient ischemic attack’—an uncommon presentation of a very common disease: a case report on capsular warning syndrome - Alvin Oliver Payus; Azliza Ibrahim; Vinushini Chandra Sheaker; Wan Nur Nafisah Wan Yahya (Oxford University Press, 2022)
Capsular warning syndrome is a rare presentation of transient ischaemic attack, which described as recurrent episodes of motor and/or sensory deficits which typically sparring the cortical function. It has a significant risk to progress into a massive stroke with permanent disability, thus important to be recognize early. Here, we report a middle-aged gentleman with no known medical illness presented with eight episodes of transient ischaemic attack within the span of 24 h. He was treated with double anti-platelet for 21 days and was not subjected to thrombolysis at time of presentation because it was outside the window period of 4.5 h and has fully recovered after each episode. The purpose of this case report is to share the uncommon clinical presentation of transient ischaemic attack, which is still not fully understood and warrant more studies especially on the treatment that can affect the progression of the disease.